Involvement of Immune Response in the Pathogenesis of Amyotrophic Lateral Sclerosis: A Therapeutic Opportunity? - Calvo, A.; Moglia, C.; Balma, M.; Chio, A. (CNS & Neurological Disorders - Drug Targets, 2010)
The immune system has been found to be involved with positive and negative effects in the nervous system of amyotrophic lateral sclerosis (ALS) patients. In general, T cells, B cells, NK cells, mast cells, macrophages, dendritic cells, microglia, antibodies, complement and cytokines participate in limiting damage. Several mechanisms of action, such as production of neurotrophic growth factors and interaction with neurons and glial cells, have been shown to preserve these latter from injury and stimulate growth and repair. The immune system also participates in proliferation of neural progenitor stem cells and their migration to sites of injury and this activity has been documented in various neurologic disorders including traumatic injury, ischemic and hemorrhagic stroke, multiple sclerosis, infection, and neurodegenerative diseases (Alzheimer's disease, Parkinson's disease and ALS). Many therapies have been shown to stimulate the protective and regenerative aspects of the immune system in humans, such as intravenous immunoglobulins, and other experimental interventions such as vaccination, minocycline, antibodies and neural stem cells, have shown promise in animal models of ALS. Consequently, several immunosuppressive and immunomodulatory therapies have been tried in ALS, generally with no success, in particular intravenous immunoglobulins. The multiple aspects of the immune response in ALS are beginning to be appreciated, and their potential as pharmacologic targets in neurologic disease is being explored.
Keywords: Amyotrophic lateral sclerosis